EVALUASI SISTEM AKUNTANSI PEMBELIAN DAN PENJUALAN BARANG DAGANG PADA PT PRIORITAS PANORAMA KOTA BENGKULU - Efriyanti, Nadya; Ummul Khair; Hernadianto, Hernadianto (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
To assess the accounting information system, especially the accounting system for purchasing and selling merchandise at PT. The priority is to evaluate the system in order to achieve the objectives, namely, to provide information for managers of new business activities, to improve information that has been produced by the existing system, to improve the level of reliability (Reability), reduce credit costs in maintaining accounting records. The research approach used in this research is a qualitative approach because the data collected is in the form of statements or descriptives that are accepted by the author. With the scope of PT. Bengkulu's priority as the object and subject of research is the parts involved in the accounting system for sales and purchases of merchandise and comparing them with theory. In this research, the type of data used is primary data. The data collection procedure involves observation, documentation and direct interviews with the research object. And the research data analysis technique used is that the accounting system used in purchasing and selling goods at PT. Priority Bengkulu has related sections, elements in accounting, and the procedures implemented in the company are quite good in accordance with the principles of a good accounting system. Even though the purchasing part of the warehouse is still less effective. Keywords: Evaluation, Purchase Accounting, Sales Accounting